Vitamin C retention in canned mango juice - Garcesto, Merlinda S.; Alabastro, Estrella F. (1982)
The objective of this two-phase vitamin study was to determine the extent of Vitamin C losses during the canning of mango juice and during its storage at room temperature. The variables considered in the storage studies was exhaust temperature and type of can. In Phase I, the percentage of loss Vitamin C during the major steps in the production of mango juice packed in 211 x 300 C-enameled can was determined. Considerable losses of the vitamin C were found to occur during extraction, pasteurization and processing, which were 9.23%, 12.13% and 10.02% respectively. A lose of 18.98% was observed as a result of holding the juice for about an hour prior to pasteurization. The total % Vitamin C lost during the production of canned mango juice was 58.52% for an 8-hour operation. Two lots of canned mango juice exhausted to two different temperatures (160 and 180°F) were stored at room temperature for six months. It was found that there was no significant difference between the two lots with respect to rate of destruction of Vitamin C and the concentration of dissolved oxygen during the 60-day storage period. In Phase II, the effect of can type on the retention of Vitamin C in canned mango juice was studied. Results show that Vitamin C retention during a six-month storage period at room temperature ranged from 42.22 to 49.67% in plain cans, while that in C-enameled cans, ranged between 21.89 and 30.07%. The dissolved oxygen concentration during the 60-day storage period did not significantly difference in the two can types. The concentrations of copper and iron in mango juice packed in plain C-enameled cans were also compared. During the six month storage period, the copper concentration was practically constant, while the iron concentration increased with storage time but with no significant difference between the two types of can.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Vitamin C; Mango juice, Canned